Early initial clinical experience with intravitreal aflibercept for wet age-related macular degeneration. (2nd May 2014) - Ferrone, Philip J; Anwar, Farihah; Naysan, Jonathan; Chaudhary, Khurram; Fastenberg, David; Graham, Kenneth; Deramo, Vincent
Abstract : Background: Age-related macular degeneration (AMD) is a degenerative process that leads to severe vision loss. Wet AMD is defined by choroidal neovascularisation, leading to the accumulation of subretinal fluid (SRF), macular oedema (ME), and pigment epithelium detachments (PED). Purpose To evaluate the initial clinical experience of conversion from bevacizumab or ranibizumab to aflibercept in wet AMD patients. Methods: Records of 250 consecutive wet AMD patients were retrospectively reviewed. Of 250 patients, 29 were naive (with no previous treatment), and 221 were previously treated with bevacizumab (1/3) or ranibizumab (2/3). On average, converted patients received 14 injections every 6 weeks on a treat-and-extend regimen with Avastin or Lucentis before being converted to aflibercept every 7 weeks on average (no loading dose) for three doses. For the purposes of this study, we concentrated on the patients converted to aflibercept since the number of naive patients was too small to draw any conclusion from. Snellen (as logMar) visual acuities, and optical coherence tomography (OCT) were compared predrug and postdrug conversion. Results: Converted patients did not show a significant difference in visual acuity or average OCT thickness from preconversion values; however, small improvements in ME (p=0.0001), SRF (p=0.0001), and PED (p=0.008) grading were noted on average after conversion to aflibercept. Conclusions: No significant difference in visual outcome or average OCT thickness was observed when switched from bevacizumab or ranibizumab q6 week to aflibercept 7-week dosing, on average. Mild anatomic improvements did occur in converted patients with regard to ME, SRF and PED improvement, on average, after conversion to aflibercept, and aflibercept was injected less frequently. No serious adverse reactions, including ocular infections or inflammation, as well as ocular and systemic effects were noted.